Exciton-polariton lasers in magnetic fields - Durnev, M. (2014)
Polariton lasers do not rely on stimulated emission of cavity photons, which sets stringent conditions on the threshold current in a conventional laser. Indeed, it has been demonstrated in optically pumped systems, that bosonic polariton lasers can outperform standard lasers in terms of their threshold power. The polaritons, which are part light and part matter quasiparticles, can undergo a condensation process into a common energy state. The radiated light from such a system shares many similarities with the light emitted from a conventional photon laser, even though the decay of the polaritons is a spontaneous process. We discuss properties of polariton lasers and condensates in GaAs based microcavities. Special emphasis is given to the system’s response to an applied magnetic field. We introduce the magnetic field interactions as a reliable tool to distinguish a polariton laser from a conventional photon laser device. In particular, we will discuss the first successful realization of an electrically pumped polariton laser, which marks a promising step towards the exploitation of polaritonic devices in the real world. We believe that our work can be extended to devices operated at room temperature by transferring the technology to large bandgap semiconductors, or even to GaAs samples with a modified layer design.